Украинская литературная теория ХХ века в контексте идеи кризиса и смерти поэтики - Червинская, Ольга (Tematy i Konteksty, 2013)
The article analyses the methodological principles according to which the Ukrainian literary discourse of the 20th century was formed. The seamlessness of this process is expounded as a natural phenomenon motivated by the historical situation and the contextual connections with the European scientific experience. The selected research aspect is related to the peculiarity of the literary text perception. At the same time, the article explains and highlights the necessity to make a fundamental distinction between hermeneutical methods and receptive poetics viewed as phenomenologically opposite methodologies, as well as the relevance of both components of the modern methodological practice to the development of the theory of intertextuality